ANALISIS PENGARUH PENGGUNAAN SMARTPHONE SAAT KULIAH TERHADAP KONSENTRASI BELAJAR MAHASISWA PGSD - Lefli Keharhua; Suci Amalia Rambe; Jesi Alexander Alim; Mitha Dwi Anggriani (CV. ADIBA AISHA AMIRA, 2025)
Smartphone use during lectures has become a common phenomenon among students, particularly those in the Elementary School Teacher Education (PGSD) Study Program. Although it can support learning, excessive smartphone use has the potential to reduce concentration. This study aims to analyze the effect of smartphone use during lectures on the concentration of PGSD students. The research method used was a quantitative survey using a Likert-scale questionnaire. The study population was PGSD students, with a sample of 20 respondents selected purposively. Data were analyzed using descriptive statistics. The results showed that smartphone use during lectures significantly affected student concentration, with the higher the intensity of smartphone use, the lower the students' concentration levels. This study emphasizes the importance of wisely managing smartphone use to prevent disrupting learning focus in class.